Are there differences in health professionals’ empathy due to academic and clinical experience? - Putrino, Natalia (2018)
Fil: Putrino, Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro interdisciplinario de investigaciones en psicología matemática y experimental; Argentina